Development of heart block in children of SSA/SSB-autoantibody-positive women is associated with maternal age and displays a season-of-birth pattern. Issue 3 (27th September 2011) - Ambrosi, Aurélie; Salomonsson, Stina; Eliasson, Håkan; Zeffer, Elisabeth; Skog, Amanda; Dzikaite, Vijole; Bergman, Gunnar; Fernlund, Eva; Tingström, Joanna; Theander, Elke; Rydberg, Annika; Skogh, Thomas; et al.
Abstract : Objective: Congenital heart block may develop in the fetuses of Ro/SSA-positive and La/SSB-positive mothers. Recurrence rates of only 10–20% despite persisting maternal antibodies indicate that additional factors are critical for the establishment of heart block. The authors investigated the influence of other maternal and fetal factors on heart block development in a Swedish population-based cohort. Methods: The influence of fetal gender, maternal age, parity and time of birth on heart block development was analysed in 145 families, including Ro/La-positive (n=190) and Ro/La-negative (n=165) pregnancies. Results: There was a recurrence rate of 12.1% in Ro/La-positive women, and no recurrence in Ro/La-negative women. Fetal gender and parity did not influence the development of heart block in either group. Maternal age in Ro/La-positive pregnancies with a child affected by heart block was, however, significantly higher than in pregnancies resulting in babies without heart block (p<0.05).Seasonal timing of pregnancy influenced the outcome. Gestational susceptibility weeks 18–24 occurring during January–March correlated with a higher proportion of children with heart block and lower vitamin D levels during the same period in a representative sample of Swedish women and a corresponding higher proportion of children with heart block born in the summer (p<0.02). Maternal age or seasonal timing of pregnancy did not affect the outcome in Ro/La-negative pregnancies. Conclusion: This study identifies maternal age and seasonal timing of pregnancy as novel risk factors for heart block development in children of Ro/La-positive women. These observations may be useful for counselling when pregnancy is considered.